A matter of trust: the royal regulation of England's French residents during wartime, 1294–13771. Issue 244 (9th January 2016) - Lambert, Bart; Ormrod, W. Mark
Abstract: This study focuses on how the English crown identified and categorized French‐born people in the kingdom during the preliminaries and first stage of the Hundred Years War. Unlike the treatment of alien priories and nobles holding lands on both sides of the Channel, the attitude to laypeople became more positive as the period progressed. In particular, the crown was prepared to grant wartime protections to French‐born residents based on evidence of local integration. Analysis of the process reveals the flexibility with which the government considered national status before the emergence of denization at the end of the fourteenth century.